Drivers of Product Boycott Among Muslim Consumers: Evidence from Indonesia - Nana, Kamsinah; Miftakhus Surur (Universitas Airlangga, 2024)
This research aims to determine the magnitude of the influence of religious values, social media, and product knowledge on the decision to boycott Unilever products among Indonesian Muslims. The research method used is quantitative with data analysis using Structural Equation Modeling-Partial Least Squares 3 (SEM-PLS). The population studied was Muslim consumers in Indonesia, and the sample was selected using a purposive sampling technique with a total of 603 respondents. The research instrument used is a questionnaire that has passed validity and reliability tests. Research findings show that religiosity, social media, and product knowledge have a significant influence on boycott decisions. For future research, it is recommended to expand the scope of variables studied by considering additional factors such as attitudes towards social issues or human value variables.